PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN REAL ESTATE - Putri Ambarwati; Kartika Hendra T; Siti Nurlaela (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
This study aims to determine the effect of good corporate governance by proxy the number of directors and the number of commissioners, leverage (DER) and company size on the performance of financial companies as measured by return on assets. The population in this study are real estate companies listed on the Indonesia Stock Exchange for the 2016–2018 period. The sample of research companies is 32 companies, the research period is 3 (three) years and the sample of this research is using purposive sampling technique. The number of research samples is 80 samples. The results of testing hypothesis 1 state that the number of directors has no effect on the company's financial performance. The results of test 2 state that the number of commissioners has an effect on the company's financial performance. The results of test 3 state that leverage (DER) has an effect on the company's financial performance. The results of test 4 state that company size has no effect on the company's financial performance.